Evaluation of changes in tidal volume during mask ventilation following administration of neuromuscular blocking drugs1. (7th May 2014) - Sachdeva, R.; Kannan, T. R.; Mendonca, C.; Patteril, M.
Summary The practice of checking the ability to mask ventilate before administering neuromuscular blocking drugs remains controversial. We prospectively evaluated the changes in the expired tidal volume during pressure‐controlled ventilation (two‐handed mask ventilation technique) as a surrogate marker to assess the ease of mask ventilation following administration of rocuronium. After informed consent, 125 patients were anaesthetised using a standard induction technique consisting of fentanyl, propofol and rocuronium, with anaesthesia then maintained with isoflurane in oxygen. The mean (SD) expired tidal volume before administration of rocuronium increased by 61 (13) ml at 2 min following onset of neuromuscular block (p < 0.001). This supports the concept that neuromuscular blockade induced by rocuronium facilitates mask ventilation.